Comparative Effectiveness of Combination Therapy with Statins and Angiotensin-Converting Enzyme Inhibitors versus Angiotensin II Receptor Blockers in Patients with Coronary Heart Disease: A Nationwide Population-Based Cohort Study in Korea - Lee, Jimin; Lee, Sukhyang (Pharmacotherapy, 2018)
Study Objective: Patients with coronary heart disease (CHD) frequently use the combination of a statin and renin-angiotensin-aldosterone system (RAAS) blocker, an angiotensin-converting enzyme inhibitor (ACEI) or angiotensin II receptor blocker (ARB), to control lipid levels and blood pressure, respectively, and the use of ARBs is increasing in Korean patients. Few studies are available, however, that have compared combination therapy with statin-ACEIs versus statin-ARBs. The objective of this study was to evaluate whether ARBs are associated with a reduced risk of major adverse cardiovascular and cerebrovascular events (MACCEs) compared with ACEIs when used in combination with statins in patients with established CHD. Design: Population-based retrospective cohort study. Data Source: Korean National Health Insurance Service–National Sample Cohort database. Patients: A total of 6577 adults who started statin-RAAS blocker combination therapy (1870 in the statin-ACEI cohort and 4707 in the statin-ARB cohort) after being diagnosed with CHD between January 2003 and December 2013 were included. Of these, 3676 propensity score–matched patients (1838 in the statin-ACEI cohort and 1838 in the statin-ARB cohort) were included in the final analyses. Measurements and Main Results: The primary outcome was MACCE (major adverse cardiovascular and cerebrovascular events), a composite of cardiovascular mortality, nonfatal myocardial infarction (MI), ischemic stroke, and revascularization. Incidences and incidence rates of MACCE were calculated to estimate the differences between the two cohorts. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated by using a Cox proportional hazard model. The incidence of MACCE was 19.9% and 14.7%, and incidence rates were 11.7 and 8.1 per 100 person-years in the statin-ACEI and statin-ARB cohorts, respectively. The risk of MACCE was significantly lower in the statin-ARB cohort (adjusted HR 0.69, 95% CI 0.59–0.81). Conclusion: A MACCE was less likely to occur in patients who received a statin-ARB than in those who received a statin-ACEI. Similar trends were seen in cardiovascular mortality and the occurrence of recurrent MI but not stroke. The availability of statin-ARB fixed-dose combinations may have contributed to the improved outcomes in the statin-ARB cohort by reducing pill burden and improving medication adherence. Further research is warranted to validate our findings and to address whether a particular statin-ARB combination is more effective than other combinations.
Keywords: Aged; Angiotensin Receptor Antagonists; Angiotensin-Converting Enzyme Inhibitors; Cardiovascular Diseases; Cerebrovascular Disorders; Cohort Studies; Coronary Disease; Databases, Factual; Drug Therapy, Combination; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Incidence; Male; Middle Aged; Republic of Korea; Retrospective Studies; Stroke; angiotensin II receptor blocker; angiotensin-converting enzyme inhibitor; coronary heart disease; major adverse cardiovascular and cerebrovascular events; statin